Infants with Down Syndrome in inclusive education - Mejía Mucha, Abigail (2021)
The research begins with a review of the literature on the importance of inclusive schooling for infants with Down syndrome over the past five years, as well as the needs and characteristics that it presents. In the same way we will see the functions and the educational methods that the inclusive school will take in the intervention and integration of these students to achieve an adequate development for their learning applying a positive development of the institutions in educational and professional fields becoming an inclusive society, breaking all kinds of barriers and imposedexclusions.